2009
DOI: 10.1002/jhet.198
|View full text |Cite
|
Sign up to set email alerts
|

Access to indoles via Diels‐Alder reactions of 2‐vinylpyrroles with maleimides

Abstract: Variously substituted 2‐vinylpyrroles underwent an endo‐addition [4+2] cycloaddition reaction with maleimides followed by a spontaneous highly diastereoselective (93–98% de) isomerization to give tetrahydroindoles in moderate to excellent yield. Treatment with activated MnO2 in refluxing toluene provided the corresponding indoles in moderate to good yield. This highly convergent methodology for formation of indoles is versatile and the starting materials are conveniently prepared. J. Heterocyclic Chem., (2009). Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
1
29
1
Order By: Relevance
“…Herein, we report direct synthesis of indoles from 65 pyrroles and 3-chloropropiophenones in a one-shot style (Scheme 1c). 70 Initially, the reaction of N-methyl-2-phenylpyrrole (1a) with 3chloropropiophenone (2a) was conducted to screen the reaction conditions (Table 1). In the presence of 10 mol % Pd(OAc) 2 as the catalyst, Cu(OAc) 2 H 2 O (6.0 equiv) as the oxidant, and NaOAc (4 equiv) as the base, the target product 3a was obtained in 41% yield from the reaction in DMSO at 100 o C (Table 1, entry 1).…”
mentioning
confidence: 99%
“…Herein, we report direct synthesis of indoles from 65 pyrroles and 3-chloropropiophenones in a one-shot style (Scheme 1c). 70 Initially, the reaction of N-methyl-2-phenylpyrrole (1a) with 3chloropropiophenone (2a) was conducted to screen the reaction conditions (Table 1). In the presence of 10 mol % Pd(OAc) 2 as the catalyst, Cu(OAc) 2 H 2 O (6.0 equiv) as the oxidant, and NaOAc (4 equiv) as the base, the target product 3a was obtained in 41% yield from the reaction in DMSO at 100 o C (Table 1, entry 1).…”
mentioning
confidence: 99%
“…Vinylpyrroles 7 and 8 (1.1 equiv) were stirred with 4‐ethylphenylmaleimide 16 in chloroform for several days, but with TLC, no reaction was observed to occur. The vinylpyrrole was used in excess because our past experience with vinylpyrroles indicated any adduct formed would be eluted during chromatography very near to the maleimide . The reaction mixtures were refluxed for five days, but still, no new TLC spots appeared; 1 H NMR confirmed that only starting materials were present in the reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…The crude 9 was then subjected to a Vilsmeier–Haack reaction , giving aldehyde 11 in 91% yield, which was conveniently vacuum‐distilled for purification; any N ‐methyl‐5‐methylthio‐2‐pyrrolecarboxaldehyde 12 that codistilled was easily removed by trituration with hexanes. Lastly, a Wittig reaction was performed on 11 by using potassium tert ‐butoxide in THF , which, following vacuum distillation, gave the desired 5‐methylthio‐2‐vinylpyrrole 13 in 69% yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations